Spatial assessment of land degradation using MEDALUS focusing on potential afforestation and reforestation areas in Ethiopia. (23rd November 2021) - Song, Cholho; Kim, Whijin; Kim, Jiwon; Gebru, Belay Manjur; Adane, Girma Berhe; Choi, Yun Eui; Lee, Woo‐Kyun
Abstract: Ethiopia currently faces severe land degradation and desertification and has attracted increasing attention for international restoration projects. However, selecting appropriate potential afforestation and reforestation areas is challenging because of limited geospatial assessment tools on a national scale. Therefore, the globally used MEDALUS approach was applied to identify areas sensitive to land degradation and desertification, and indices were utilized to establish the main drivers from 2000 to 2019. The value of the environmentally sensitive area index (ESAI) ranged from 1 to 1.58. Addis Ababa, Afar, Somali, and Tigray had relatively high ESAI values, approaching the over 1.42 which regarded critical thresholds. However, the main driver of land degradation and desertification was identified as the management quality index (MQI) and the analysis of relationships indicated that the climate quality index, soil quality index, and MQI caused changes in the vegetation quality index. Increasing housing, agricultural transitions, and urbanization, were identified by on‐site visual interpretation. Even though some land cover changes and fluctuations of the indices existed on a national scale, the deforestation areas in Amhara, Benshangul‐Gumaz, and Oromia West have the highest priority for forest restoration projects. Thus, international attention to afforestation and reforestation clean development mechanism (A/R CDM) and reducing emission from deforestation and forest degradation (REDD+) is required to combat desertification and to secure land degradation neutrality in Ethiopia.